IMPROVING SCIENCE LEARNING OUTCOMES THROUGH THE MAKE A MATCH MODEL IN ELEMENTARY SCHOOLS - irna ayenda (Teaching and General Education Studies, 2026)
This study aims to apply the Make a Match type of cooperative learning model to improve Natural Science (IPA) learning outcomes of fourth-grade students at SD Negeri 61 Lubuklinggau. Based on initial observations, students experienced difficulties in understanding science concepts when learning was dominated by lecture-based methods, resulting in low learning outcomes and limited classroom participation. The study employed Classroom Action Research (CAR) using the Kemmis and McTaggart model, conducted in two cycles consisting of planning, action, observation, and reflection stages. The research subjects were 25 fourth-grade students. Data collection techniques included pre-tests, post-tests, and classroom observations. In Cycle I, the average pre-test score was 52, with only 20% of students achieving mastery, while the post-test average increased to 69.2, with 68% of students achieving mastery. In Cycle II, the post-test results showed a further improvement, with an average score of 87.6 and 88% of students achieving mastery. These results demonstrate a significant improvement in students’ science learning outcomes after the implementation of the Make a Match learning model. In conclusion, the Make a Match cooperative learning model is effective in improving students’ science learning outcomes while simultaneously increasing learning motivation and active participation. This study implies that cooperative and game-based learning models can serve as effective alternatives to traditional teaching methods in elementary science instruction. Future research is recommended to apply the Make a Match model to other science topics, grade levels, or subjects to examine its broader applicability and long-term impact